Protease Supplementation and its Effect on Performance and Nutrient Utilization in Broiler Chicken Fed Low Protein Diets - Salman, Chisty Syed; Nayak, Sunil; Baghel, R.P.S.; Malapure, C. D.; Govil, Kumar; Thakur, Dinesh (Indian Journal of Animal Nutrition, 2017)
The present experiment was designed to evaluate the effects of protease supplementation on performance, nutrient utilization, carcass traits and economics of broilers production. A total of 216, day old chicks were randomly assigned to nine dietary treatments and each treatment consisted of three replicates of eight chicks each. The basal diet (T1) was formulated as per ICAR (1998) specifications and contained 22% CP and 2800 kcal ME/kg diet. In treatment T2, CP content was reduced to 20%. In treatments T3, T4 and T5 the diets were same as in treatment T2 but supplemented with proteases (each g contained 600000 IU) @ 100, 200 and 300 g/tonne of feed, respectively. In treatment T6, the diet was same as in treatment T1 except CP content which wasfurther reduced to 18%. In treatments T7, T8 and T9, the diets were same as in T6 but supplemented with protease @ 100, 200 and 300 g/tonne, respectively. The experiment was conducted for 5 weeks. The broilers fed with standard basal diet (22% CP) had a better (P